2014
DOI: 10.4049/jimmunol.1302702
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine Deficiency Promotes T Cell Infiltration in Experimental Autoimmune Encephalomyelitis: The Involvement of CCL2

Abstract: Multiple sclerosis (MS) is a complex multifactorial disease that results from the interplay between environmental factors and a susceptible genetic background. Experimental autoimmune encephalomyelitis (EAE) has been widely used to investigate the mechanisms underlying MS pathogenesis. Chemokines, such as C-C Chemokine Ligand 2 (CCL2), are involved in the development of EAE. We have previously shown that thiamine deficiency (TD) induced CCL2 in neurons. We hypothesized that TD may affect the pathogenesis of EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 69 publications
0
32
0
1
Order By: Relevance
“…Various vitamins have also been examined for their effects on EAE [24,25]. One study showed that vitamin D3 supplementation significantly inhibited the incidence and severity of MBP-induced EAE in female B10.PL mice, compared to unsupplemented female mice and male mice with or without supplementation, a difference thought to be due to a gender difference in vitamin D3 metabolism within the CNS [24].…”
Section: Discussionmentioning
confidence: 99%
“…Various vitamins have also been examined for their effects on EAE [24,25]. One study showed that vitamin D3 supplementation significantly inhibited the incidence and severity of MBP-induced EAE in female B10.PL mice, compared to unsupplemented female mice and male mice with or without supplementation, a difference thought to be due to a gender difference in vitamin D3 metabolism within the CNS [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, TD-induced neuroinflammation not only involves astrocytes, but also neurons, microglia, and endothelia cells. As previously demonstrated, TD produces a mild, chronic impairment of oxidative metabolism and reduced activities of the thiamine-dependent mitochondrial enzymes (1). TD causes regionally selective neuronal death and activation of astrocytes, microglia, and endothelial cells, which are also observed in various neurodegenerative disorders (1).…”
mentioning
confidence: 76%
“…As previously demonstrated, TD produces a mild, chronic impairment of oxidative metabolism and reduced activities of the thiamine-dependent mitochondrial enzymes (1). TD causes regionally selective neuronal death and activation of astrocytes, microglia, and endothelial cells, which are also observed in various neurodegenerative disorders (1). TD induces a time-dependent chronic impairment of oxidative metabolism that initiates a cascade leading to selective neuronal loss that occurs first in the submedial thalamic nucleus in mice (2) and the mammillary bodies, the periaqueductal area, the periventricular region of the third ventricle, and the paramedian thalamic nuclei in humans (3).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…In a mouse model of MS, experimental autoimmune encephalomyelitis (EAE) induced by, myelin oligodendrocyte glycoprotein encephalitogenic peptide, MOG35-55, the disease severity is exacerbated in thiamine deficient mice compared to non-thiamine deficient mice. The deficient mice showed pathologic alterations in the spinal cord, microglial activation and increased Th1 and Th17 cell infiltration and increased expression of chemokine, CCL2, and its receptor in the spinal cord [23]. Thus, there is preliminary evidence that suggests some potential role of thiamine in MS, however these need to be substantiated in larger studies.…”
Section: The Role Of Vitamin B1 (Thiamine) In Msmentioning
confidence: 89%